Low-Temperature Aging Provides 22% Efficient Bromine-Free and Passivation Layer-Free Planar Perovskite Solar Cells - Wang, Xin; Wang, Luyao; Shan, Tong; Leng, Shibing; Zhong, Hongliang; Bao, Qinye; Lu, Zheng‑Hong; Deng, Lin‑Long; Chen, Chun‑Chao (Nano-Micro Letters, 2020)
Previous reports of formamidinium/methylamine (FAMA)-mixed halide perovskite solar cells have focused mainly on controlling the morphology of the perovskite film and its interface—for example, through the inclusion of bromine and surface passivation. In this paper, we describe a new processing pathway for the growth of a high-quality bromine-free FAMAPbI3 halide perovskites via the control of intermediate phase. Through low-temperature aging growth (LTAG) of a freshly deposited perovskite film, α-phase perovskites can be seeded in the intermediate phase and, at the same time, prevent beta-phase perovskite to nucleate. After postannealing, large grain-size perovskites with significantly reduced PbI2 presence on the surface can be obtained, thereby eliminating the need of additional surface passivation step. Our pristine LTAG-treated solar cells could provide PCEs of greater than 22% without elaborate use of bromine or an additional passivation layer. More importantly, when using this LTAG process, the growth of the pure alpha-phase FAMAPbI3 was highly reproducible. Article Highlights: 1 By low-temperature aging, superior bromine-free FA1–xMAxPbI3 perovskite film is realized. 2 By suppressing lead iodide on the surface of perovskite, no further passivation step or layer is needed. The efficiency of planar perovskite solar cells is improved to 22.41% with robust reproducibility.